DESKRIPSI KESALAHAN MAHASISWA DALAM MENGGAMBAR TITIK KOORDINAT PADA DIMENSI DUA DAN DIMENSI TIGA - Patricia, Firda Alfiana (Universitas Insan Budi Utomo, 2021)
This study aims to describe the errors found in students when drawing coordinates in the two and three dimensions in the Analytical Geometry course. The research subjects were 20 students of the Mathematics Education study program at IKIP Budi Utomo Malang Class 2019A consisting of 14 women and six men whose determination was made using simple random sampling. Fifteen students who made mistakes and five students who were correct in drawing the coordinates in the second dimension, while in drawing the coordinates in the third dimension, 12 students made mistakes and eight students who were correct. Based on data analysis using discourse analysis, the errors found were process skills errors, including not using grid paper so that the distance between points is not the same, coordinate points are not named, coordinate points are not written, numbers on the coordinate axes are not written. and mistakenly drew the correct coordinate axes.